2008
DOI: 10.1111/j.1741-3737.2008.00485.x
|View full text |Cite
|
Sign up to set email alerts
|

Relative Spousal Earnings and Marital Happiness Among African American and White Women

Abstract: The distinctive economic histories of African American and White wives suggest that involvement in household income production holds contextually situated unique meanings for these groups. Yet research has not addressed racial differences in the effects of relative earnings on marital well‐being. Surveying 431 employed wives in 21 U.S. cities, we found that wife‐to‐husband income ratio and marital happiness were negatively associated when women held traditional values, but in racially distinct ways. Among Whit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 36 publications
3
56
0
4
Order By: Relevance
“…Historically, men occupied a better position in the labor market, so couples relying on earning capacity will maximize their economic rewards; whilst a woman's contribution is maximized through their dedication to domestic work and children care. Based on this economic function and exchange approach, couples who do not follow this gender-based specialization model would be at a disadvantage in both the economic and domestic spheres, which may lead to lower marital happiness (Furdyna et al 2008). The scenario is that an increase in wives' actual income and relative contributions may increase the sense of perceived unfairness over the households division of labor, challenge their husbands' power as head of the household, and cause them to experience greater marital dissatisfaction (Rogers 2004).…”
Section: Wives' Relative Income and Marital Happinessmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, men occupied a better position in the labor market, so couples relying on earning capacity will maximize their economic rewards; whilst a woman's contribution is maximized through their dedication to domestic work and children care. Based on this economic function and exchange approach, couples who do not follow this gender-based specialization model would be at a disadvantage in both the economic and domestic spheres, which may lead to lower marital happiness (Furdyna et al 2008). The scenario is that an increase in wives' actual income and relative contributions may increase the sense of perceived unfairness over the households division of labor, challenge their husbands' power as head of the household, and cause them to experience greater marital dissatisfaction (Rogers 2004).…”
Section: Wives' Relative Income and Marital Happinessmentioning
confidence: 99%
“…Over the past decades, the impact of women's income on marital outcomes has been studied intensively in the west, and the mainstream line of study supported the economic independence hypothesis (Parsons 1949), that is, wives' relative income will lead to their marital dissatisfaction (Furdyna et al 2008) and it is positively associated with the risk of divorce (Heckert et al 1998;Rogers and Deboer 2001;Kalmijn et al 2007). However, another line of study suggested that wives' income would add capital and assets to the marriage and enhance the quality of life for the family.…”
Section: Introductionmentioning
confidence: 99%
“…The positive effect of maternal education level on children's adjustment is consistent across cultures. However, previous research findings regarding the impact of maternal education level on marital conflict have varied according to the sample studied (Bean et al 1996;Furdyna et al 2008;Schoen et al 2006). The relationship between maternal education level and marital conflict was found to be positive among Mexican-Americans (Bean et al 1996).…”
Section: Discussionmentioning
confidence: 94%
“…The impact of women's income on marital outcomes has been studied intensively in the west, and the mainstream line of study supported the economic independence hypothesis (Parsons, 1949), i.e., wives' relative income (WRI) will lead to their marital dissatisfaction (Furdyna, Tucker, & James, 2008) and it is positively associated with the risk of divorce (Heckert, Nowak, & Snyder, 1998;Rogers & Deboer, 2001;Kalmijn, Loeve, & Manting, 2007). Equity theory argued that the negative impact of WRI on the wife's marital quality can be understood by her lowered perception of equity (Booth, Johnson, White, & Edwards, 1984;Schafer & Keith, 1981).…”
Section: Introductionmentioning
confidence: 95%
“…Historically, men occupied a better position in the labor market, so couples relying on earning capacity will maximize their economic rewards, while a woman's contribution is maximized through their dedication to domestic work and children care. Based on this economic function and exchange approach, couples who do not follow this gender-based specialization model would be at a disadvantage in both the economic and the domestic spheres, which may lead to lower marital satisfaction (Furdyna et al, 2008). The stability of marriage would be threatened if the wives earned more than their husbands or had higher occupational prestige (Parsons, 1949).…”
Section: Resource Exchange Theorymentioning
confidence: 99%